Milk protein polymorphism in Swiss dairy cattle - Taha, Fawzy; Puhan, Zdenko (Agricultural and Food Science, 1993)
Individual cow milk samples from (a) 208 original Swiss Simmental (OSS), (b) 220 of their crosses (Simmental cattle = FV) with American Red Holstein (RH), (c) 215 original Swiss Brown (OSB) and (d) 390 of their crosses (Brown cattle = BV) with American Brown Swiss (BS) were genotyped for the variants of milk caseins (Cn) and β-Lactoglobulin (β-Lg). In addition, the association between κ-Cn genotypes and milk yield was studied. Reasonable differences in the allele frequencies were found between the breeds. Compared to pure-bred OSS, crossing with RH resulted in a decrease in the frequencies of αs1-Cn C, β-Cn B and κ-Cn B and in an increased frequency of β-Lg B. Within OSB, increased crossing with BS resulted in a decrease in the frequencies of αs1-Cn C and β-Cn B and in increased frequencies of κ-Cn B and β-Lg B. A significant association between the κ-Cn locus and milk yield could only be shown for the OSS breed.